Judges as Agents of Change: The Role of the Judiciary in Protecting Vulnerable Groups (Indonesian Court and Justice Review, 2024)
Judges in Indonesia play a crucial role, not only as legal decision-makers but also as agents of social change, particularly in the protection of vulnerable groups such as women, children, minorities, and marginalized communities. This study explores how the Indonesian judiciary addresses the rights of these groups, focusing on the ways in which judicial decisions impact their protection through legal interpretations, rulings, and the evolution of case law that fosters inclusivity and equality. Through a mixed-methods approach, this research combines a detailed analysis of key judicial decisions with interviews from legal professionals, advocates, and individuals from vulnerable groups to understand how judges navigate complex social issues such as discrimination, gender-based violence, and socio-economic inequality. The findings suggest that while the Indonesian judiciary has made significant strides in safeguarding the rights of vulnerable populations, challenges remain, particularly due to inconsistent legal interpretations, societal biases, and political pressures. This study's novelty lies in its investigation of judicial behavior through the lens of social responsibility, considering not only the application of legal norms but also the broader social implications of judicial decisions. The urgency of this research is emphasized by the increasing calls for judicial reform in Indonesia and the necessity of ensuring that the judiciary effectively addresses systemic injustices. Ultimately, this research provides valuable insights into how judges in Indonesia can act as agents of progressive change, offering recommendations for judicial education, strengthening human rights advocacy, and enhancing legal frameworks to ensure better protection for vulnerable groups.